The limits of social science causal explanation and value relevance - Hammersley, Martyn (Los Angeles Sage, 2014)
What forms of knowledge can social science claim to produce? Does it employ causal analysis, and if so what does this entail? What role should values play in the work of social scientists? These are the questions addressed in this book. They are closely interrelated, and the answers offered here challenge many currently prevailing assumptions. They carry implications both for research practice, quantitative or qualitative, and for the public claims that social scientists make about the value of their work. The arguments underpinning this challenge to conventional wisdom are laid out in detail in the first half of the book. In later chapters their implications are explored for two substantive areas of intrinsic importance: the study of social mobility and educational inequalities; and explanations for urban riots, notably those that took place in London and other English cities in the summer of 2011.--Provided by publisher.
Introduction -- Causation and qualitative inquiry -- The problem of explanation in social science: A Weberian solution? -- On the role of values in social research -- From facts to value judgments? A critique of critical realism -- Can social science tell us whether a society is meritocratic? A Weberian critique -- We didn't predict a riot! On the public contribution of social science.
Includes bibliographical references (pages 149-170) and indexes.
Keywords: Social sciences -- Research; Social sciences -- Philosophy